PELATIHAN PENINGKATAN RASA NASIONALISME SISWA KELAS 4 DAN 5 MELALUI KEGIATAN MENGARANG PUISI - SAGALA, LASMA HATI BORU; FARADILLA, FADIYAH; RAMADHAN, AFIFAH ARLIA; AMALIAPUTRI, AYUDYA WAHYU; SAKRE, TANTRA (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2023)
Education has an important role in the continuity of the teaching and learning process. The teacher's role in instilling a sense of nationalism in students can be realized through Indonesian language subjects, poetry composing activities. Composing poetry is part of the writing lessons taught in schools, both at primary and secondary levels. Students consider the poetry material contained in learning Indonesian Language and Literature to be difficult to learn, starting from analyzing poetry, interpreting poetry, reading poetry, to writing poetry. Based on the observation data obtained when learning poetry writing skills at SDN Krembung 1, there is still a need for guidance and development in practicing skills in expressing ideas into poetry. The expected objectives of this program are: (1) increasing students' knowledge in writing poetry; (2) increase students' motivation in writing poetry; and (3) improve students' skills in writing poetry. ABSTRAKPendidikan memiliki peran penting dalam keberlangsungan proses belajar mengajar. Peran guru dalam menanamkan rasa nasionalisme siswa dapat diwujudkan melalui mata pelajaran Bahasa Indonesia kegiatan mengarang puisi. Mengarang puisi merupakan bagian dari pembelajaran menulis yang diajarkan di sekolah, baik pada tingkat dasar ataupun menengah. Siswa menganggap materi puisi yang terdapat dalam pembelajaran Bahasa dan Sastra Indonesia sulit untuk dipelajari, mulai dari menganalisa puisi, memaknai puisi, membaca puisi, hingga menulis puisi. Berdasarkan perolehan data observasi saat pembelajaran keterampilan menulis puisi di SDN Krembung 1 masih memerlukan pembinaan dan pengembangan dalam melatih kecakapan menuangkan ide ke dalam bentuk puisi. Tujuan yang diharapkan dari program ini yaitu: (1) meningkatkan pengetahuan siswa dalam menulis puisi; (2) meningkatkan motivasi siswa dalam menulis puisi; dan (3) meningkatkan keterampilan siswa dalam menulis karya puisi.